Activation of the GLP-1 receptors in the nucleus of the solitary tract reduces food reward behavior and targets the mesolimbic system. - Jennifer E Richard; Rozita H Anderberg; Andreas Göteson; Fiona M Gribble; Frank Reimann; Karolina P Skibicka (PLoS ONE)
The gut/brain peptide, glucagon like peptide 1 (GLP-1), suppresses food intake by acting on receptors located in key energy balance regulating CNS areas, the hypothalamus or the hindbrain. Moreover, GLP-1 can reduce reward derived from food and motivation to obtain food by acting on its mesolimbic receptors. Together these data suggest a neuroanatomical segregation between homeostatic and reward effects of GLP-1. Here we aim to challenge this view and hypothesize that GLP-1 can regulate food reward behavior by acting directly on the hindbrain, the nucleus of the solitary tract (NTS), GLP-1 receptors (GLP-1R). Using two models of food reward, sucrose progressive ratio operant conditioning and conditioned place preference for food in rats, we show that intra-NTS microinjections of GLP-1 or Exendin-4, a stable analogue of GLP-1, inhibit food reward behavior. When the rats were given a choice between palatable food and chow, intra-NTS Exendin-4 treatment preferentially reduced intake of palatable food but not chow. However, chow intake and body weight were reduced by the NTS GLP-1R activation if chow was offered alone. The NTS GLP-1 activation did not alter general locomotor activity and did not induce nausea, measured by PICA. We further show that GLP-1 fibers are in close apposition to the NTS noradrenergic neurons, which were previously shown to provide a monosynaptic connection between the NTS and the mesolimbic system. Central GLP-1R activation also increased NTS expression of dopamine-β-hydroxylase, a key enzyme in noradrenaline synthesis, indicating a biological link between these two systems. Moreover, NTS GLP-1R activation altered the expression of dopamine-related genes in the ventral tegmental area. These data reveal a food reward-suppressing role of the NTS GLP-1R and indicate that the neurobiological targets underlying food reward control are not limited to the mesolimbic system, instead they are distributed throughout the CNS.